The Concept Of Silence After Ijab In Marriage Ceremonies: The Perspective Of Sheikh Muhammad Arsyad Al-Banjari In Kitab Nikah - Mohammad Ridwan; Fazri Rahmadani; Ahmad Risandi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
The tradition of "remaining silent after ijab" is a local marriage practice still observed in parts of the Banjar community. This study aims to explore Sheikh Muhammad Arsyad al-Banjari's perspective on this practice as found in his Kitab Nikah. The research uses a library study method with a normative-juridical approach and textual analysis of classical Islamic texts. The findings show that while Sheikh Muhammad Arsyad does not explicitly address the silence tradition in formal legal terms, he strongly emphasizes the necessity of continuity and immediacy between the ijab (offer) and qabul (acceptance) as essential for a valid marriage contract. This suggests that the silence practice is more of a cultural custom, which remains acceptable in Islamic law as long as it does not obscure the clarity and intent of the marriage contract. This study highlights the importance of contextual understanding of local fiqh and its connection to socio-religious practices within the community.